Planning the use of augmented and virtual reality for Vocational Education and Training : a practical guide - Goertz, Lutz [Verfasser]; Hagenhofer, Thomas [Verfasser]; Fehling, Christian Dominic [Verfasser]; Hanau, Eva [Herausgeber] (Federal Institute for Vocational Education and Training, 2021)
"The English publication "Planning the Use of Augmented and Virtual Reality for VET - A Practical Guide" offers interested readers a systematic overview of possible learning scenarios for immersive technologies in vocational education and training. On the basis of practical examples from Germany, possible learning goals, didactic methods and target groups are presented. Furthermore, a checklist provides guidance regarding content-related, technical, organizational and legal aspects that need to be taken into account when planning and implementing AR/VR-based learning applications in VET." (Editor ; BIBB-Doku)
Keywords: L 4 Medien & Technologien; G 2.2.1 Technologisierung; 370; Berufsbildung; Augmented Reality; virtuelle Realität; Mensch-Maschine-Kommunikation; Assistenzsystem